Empowering Consumers Through Data and Smart Technology: Experimental Evidence on the Consequences of Time‐of‐Use Electricity Pricing Policies. (8th July 2016) - Harding, Matthew; Lamarche, Carlos
Abstract: This paper investigates the extent to which technology used to automate household responses to time‐of‐use pricing for electricity leads to higher energy savings than simply providing households with information on current prices and quantities. Using a large randomized field trial, we find that informed households with "smart" thermostats achieve impressive reductions in consumption during on‐peak periods of up to 48 percent, but also engage in substantial load shifting to off‐peak hours. We also document the extent to which household responses to time‐of‐use pricing are heterogeneous and vary significantly by demographics, weather, and across the usage distribution .